2019
DOI: 10.1021/acs.energyfuels.9b00739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Roughness on the Contact Angle due to Calcite Dissolution in an Oil–Brine–Calcite System: A Nanoscale Analysis Using Atomic Force Microscopy and Geochemical Modeling

Abstract: Low-salinity water flooding appears to be a promising means to improve oil recovery in carbonate reservoirs because of a wettability alteration process. Contact angle measurement is a direct approach to reveal the wettability alteration in an oil–brine–carbonate system. However, questions have been raised about using contact angle measurement to justify the wettability alteration. This is because the contact angle may be significantly affected by surface roughness variation in the presence of low-salinity wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…It is worth noting that we saturated the deionized water with calcite to prevent any effect on the new calcite surface during cleaning. Also, it is noteworthy that the surface roughness of the new calcite surface used in this work is in a range of 4 to 7 nm, which has been reported in our previous work [44].…”
Section: Calcitesupporting
confidence: 70%
“…It is worth noting that we saturated the deionized water with calcite to prevent any effect on the new calcite surface during cleaning. Also, it is noteworthy that the surface roughness of the new calcite surface used in this work is in a range of 4 to 7 nm, which has been reported in our previous work [44].…”
Section: Calcitesupporting
confidence: 70%
“… 45 , 46 In a work by Al Maskari et al, 45 it was observed that surface roughness (∼17 nm) caused by calcite dissolution did not greatly influence the wettability alteration trends caused by low salinity water on calcite substrates. Rather, Al Maskari et al 45 proposed that the electrostatic interactions at the nanoscale were strong and served as the driver for the observed changes in calcite wettability. In further analysis aimed at increasing the surface roughness, Sari et al 46 observed that at higher roughness (∼945 nm), the wetting state of the calcite rock was affected.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 Our previous work shows a surface roughness with a range of 4−7 nm on a new calcite surface, which plays a minor role in adhesion forces. 58 To remove small calcite particles from the new calcite substrate, deionized water equilibrated with CaCO 3 was used to rinse all the new calcite surfaces.…”
Section: ■ Experimental Methodologymentioning
confidence: 99%
“…In this research, we used Iceland Spar calcite crystal to represent carbonate substrate in the adhesion force experiments (AFM) and contact angle experiments. Prior to all the AFM and contact angle experiments, the Iceland Spar calcite crystals were cleaved to gain a new clean calcite surface, which can help to eliminate the impact of surface roughness on the results of the experiments. , Our previous work shows a surface roughness with a range of 4–7 nm on a new calcite surface, which plays a minor role in adhesion forces . To remove small calcite particles from the new calcite substrate, deionized water equilibrated with CaCO 3 was used to rinse all the new calcite surfaces.…”
Section: Experimental Methodologymentioning
confidence: 99%